Investigation of the neuroprotective effects of bee-venom acupuncture in a mouse model of Parkinson’s disease by using immunohistochemistry and In-vivo 1H magnetic resonance spectroscopy at 9.4 T - Yoon, Moon-Hyun; Lee, Do-Wan; Kim, Hyun-Jin; Chung, Jin-Yeung; Doo, Ah-Reum; Park, Hi-Joon; Kim, Seung-Nam; Choe, Bo-Young (Journal of the Korean Physical Society, 2013)
Neuroprotective therapeutics slows down the degeneration process in animal models of Parkinson’s disease (PD). The neuronal survival in PD animal models is often measured by using immunohistochemistry. However, dynamic changes in the pathology of the brain cannot be explored with this technique. Application of in-vivo 1H magnetic resonance spectroscopy (1H MRS) can cover this shortcoming, as these techniques are non-invasive and can be repeated over time in the same animal. Thus, the sensitivity of both techniques to measure changes in the PD pathology was explored in an experiment studying the neuroprotective effects of the vigilance enhancer bee-venom (BV) in a mouse model of PD. The mice were pre-treated with 0.02-ml BV administered to the acupuncture point GB34 (Yangneungcheon) once every 3 days for 2 weeks. Three groups were classified as control, MPTP-intoxicated PD model and BV-treated mice. Outer volume suppression combined with the ultra-short echo-time STEAM (TE = 2.2 ms, TM = 20 ms, TR = 5000 ms) was used for localized in-vivo 1H MRS. Based on the 1H MRS spectral analysis, substantial changes of the neurochemical profiles were evaluated in the three investigated groups. In particular, the glutamate complex (Glx)/creatine (Cr) ratio (7.72 ± 1.25) in the PD group was significantly increased compared to that in the control group (3.93 ± 2.21, P = 0.001). Compared to the baseline values, the Glx/Cr ratio of the BV-treated group was significantly decreased 2 weeks after MPTP intoxication (one-way ANOVA, p < 0.05). In conclusion, the present study demonstrated that neurochemical alterations occurred in the three groups and that the neuroprotective effects of the BV acupuncture in a mouse model of PD could be quantified by using immunohistochemistry and 1H MRS. KCI Citation Count: 0